Real world outcomes of neoadjuvant chemotherapy and radiotherapy for borderline resectable pancreatic cancer: a multicentre observational study. Issue 11 (23rd August 2021) - Parsonson, Andrew Ohyama; Connolly, Elizabeth; Lee, Mark; Hruby, George; Sandroussi, Charbel; Merrett, Neil; Samra, Jaswinder; Mittal, Anubhav; Tse, Regina; Grimison, Peter
Abstract: Background: Neoadjuvant therapy may increase the likelihood of complete (R0) resection for borderline resectable pancreatic cancer. The optimal approach is unknown and differs amongst treatment centres. Methods: We identified patients with biopsy‐proven borderline resectable pancreatic adenocarcinoma who commenced neoadjuvant therapy between January 2012 and June 2019 at three centres in Sydney, Australia. Patterns of care and outcomes of varying approaches were examined. Results: Forty‐eight patients were identified. Median age was 66 years (range: 41–84). Staging included endoscopic ultrasound in 98%, PET‐CT scan in 77%, laparoscopy in 46%. Neoadjuvant regimens used were a combination of chemotherapy and chemo‐radiation (58%), chemotherapy alone (13%) and chemoradiation alone (29%). Radiologic complete or partial response occurred in 33% and progression in 25%. Complete macroscopic surgical resection was achieved in 50%, and R0 resection in 38%. At median follow‐up of 15 months, the 1‐year and 2‐year overall survival was 75% and 63% respectively, and the 1‐year and 2‐year progression‐free survival was 50% and 29% respectively. Significant predictors of macroscopic resectability were radiologic response ( p  = 0.005) but not addition of radiotherapy to chemotherapy (OR 0.87, p  = 0.81). Predictors of overall survival included baseline Ca19.9 level ( p  = 0.04) and a trend to the use of systemic chemotherapy (HR 0.51, p  = 0.07), but not use of radiotherapy (HR 0.70, p  = 0.47). Conclusion: There is high variability in staging and neoadjuvant approaches for borderline resectable pancreas cancer. Despite aggressive neoadjuvant therapies, R0 resection and prolonged survival are uncommon. The incremental benefit of neoadjuvant radiotherapy after neoadjuvant chemotherapy was not demonstrated in this observational study. Abstract : There is high variability in staging and neoadjuvant approaches for borderline resectable pancreatic adenocarcinoma. Despite aggressive neoadjuvant therapies, R0 resection and prolonged survival are uncommon. Further research to determine the optimal neoadjuvant treatment approach for borderline resectable pancreatic cancer is required.